PENERAPAN PERANGKAT PEMBELAJARAN YANG TERINTEGRASI ERA SOCIETY 5.0, MELALUI PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE (AI) PADA KELOMPOK KERJA GURU (KKG) PABUARAN - Umalihayati, Umalihayati; Rahmadani, Kurniati; Andriani, Rina; Imamudin, Imamudin; Putri, Intan Chania; Audi, Nadia Putri (LPPM Universitas Bina Bangsa, 2024)
The aim of PKM activities is to develop practical activities of the Teacher Working Group (KKG) in Pabuaran District, which are able to meet the needs of elementary school teachers, so that they are expected to be more dynamic and functional by implementing integrated learning tools Era Society.5.0, through the use of Artificial Intelligence, which is very necessary for elementary school teachers in Pabuaran Serang District. Implementation method: Socialization of the PKM Program in the form of analysis of the situation and conditions of target partners, Application of Technology, Training, Partner Participation, Evaluation and Program Sustainability. Results of PKM activities: The results of this activity are increased KKG activities in Pabuaran District which can result in the need for elementary school teachers up to 80%, an increase in integrated learning tools Era.Society.5.0, up to 80%, an increase in the application of science and technology-based learning methods, Artificial Intelligence (AI ) until it reaches 80%, the PKM Team will continue to provide assistance to Pabuaran KKG target partners